ZPR of the Olo river: management of sport fishing - Martinho, António (2018)
This work is the result of sport fishing monitoring carried out in 2013 in the Reserved Fisheries Zone (ZPR) of the Olo River. The aim of this initiative was to evaluate whether the management model, initially established, would require, after six years of implementation, eventual modifications, and to stabilize, in a Management Plan, the recreational sport fishing activity during the next years of activity. This study respected the methodology originally adopted (2007). In the conservation status assessment of the fish communities, the data concerning age, growth, physical condition and their relationship with the different habitat types where they were captured were analyzed. The results showed that the brown trout and the northern chub are once more the species with the most spatial distribution (found along the entire river). Also, revealed that the salmonid was present in all the sampling stations with water available throughout the year. The recent occurrence of a trout specimen at the age of 6+, in a monitoring action, determined the increase in 2016 of one year in the maximum longevity obtained by this species. In 2013, Gobio lozanoi had a strong expression in the lower section (1/3) of the river, especially with very young individuals (0+). Its occurrence is strongly associated with anthropic actions (illicit introductions) in more lentic habitats, where the water temperature is higher in summer. Overall, the longitudinal variation of the species is directly associated with the quality of the freshwater habitat. It was also possible to assess the pertinence of the adoption of complementary measures to improve the sustainable management of sport fishing in the Olo River ZPR (Ordinance no. 206/2008, of February 25), which are proposed in the Plan Management of the Olo River ZPR.